The principle of double conformity as a ground for inadmissibility of the appeal - Cadillo Ponce, José Daniel (2023)
The rules of the admissibility of the appeal have varied; That remedy is now much more restrictive. One of these changes relates to the socalled principle of double conformity. That is, if in a given proceeding there is a certain ruling at first instance and it is confirmed at second instance, the appeal would not proceed; However, there are exceptions. One of these is the opposition of the appealed resolution to the jurisprudential doctrine of the Supreme Court, as is the case of due process.